A Mouse Model of Cancer Induced Bone Pain: From Pain to Movement - Ji, Haiwang; Jin, Xiang; Zhang, Qing; Zhou, Yuan; Zhu, Chan; Yang, Yan; Tang, Zongxiang; Yu, Guang; Wang, Changming (Frontiers in Behavioral Neuroscience, 2022)
Cancer induced bone pain (CIBP) occurs in patients with advanced osteosarcoma or metastasized bone tumors can negatively affects the patient’s quality of life. However, motor impairment in CIBP is still understudied. To improve the CIBP patients’ quality of life, the study of CIBP induced movement impairment is of particular importance. Here, we presented a model of metastatic cancer induced bone pain caused by allograft of Lewis lung cancer cells. In this method, we injected Lewis lung cancer cells into the femoral medulla cavity and recorded the pain behavior and motor behavior after CIBP surgery. We observed enhanced pain after the initial surgery. Interestingly, we found the latency on rotarod was significantly reduced concomitant with tumor growth and pain. This result indicated that the motor coordination and balance were severely impaired in cancer induced bone pain. We also found the pain and motor behavioral differences in models that severed the patellar ligament vs maintaining the patellar ligament. These findings provide a novel clue for further investigating the mechanisms responsible for the generation and development of CIBP.